Influencia de la temperatura y tiempo de secado de la harina de sangre en su contenido final de humedad y proteína - De La Cruz Briceño, Rubén Iván (2006)
The present work had as main objective to determine the effect of the temperature and time of drying in samples of blood of bovine livestock, and its influence in the final content of proteins and humidity of the same one. In a same way it is determined the design parameters from the drying equipment vacuum, starting from the operation parameters using samples of blood of bovine livestock, having like base the temperature and the good time of operation. Experimentally it was demonstrated the direct influence of the temperature and time of drying in the final content of humidity and protein of the flour of blood. For the execution of the experiment we used a prototype of 1,0 L of capacity, built in stainless steel AISI 304, with vacuum system, made up of a vacuum pump of ¼ HP, 220V, a condenser and an electric kitchen of resistance. The results showed a very best temperature of 50ºC, a vacuum of 21 inch of Hg and a time of 18,80 minutes to obtain samples with the biggest contained of proteins and percentage of humidity of 9,8. The protein contained of the blood is affected with the temperature according to the equation: %P = 0,0204T² - 4,2765T + 243,29 The time of drying is proportional to the vacuum used in the dryer according to the equation: t = - 0,1015P² + 2,0885P + 20,398 We got a dry blood of dark brown color was obtained with a content of: 81,20% protein; 9,80% of humidity; 2,80% of fat, 5,80% of ashes